Implementasi Model Discovery Learning Dipadu Modul Sistem Ekskresi Berbasis Konstruktivisme untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Yennita Yuliani*; Hasanuddin Hasanuddin; Safrida Safrida; Khairil Khairil; Andi Ulfa Tenri Pada (Jurnal Pendidikan Sains Indonesia, 2021)
The learning process at SMAN 1 Kluet Utara and SMAN 1 Kluet Selatan, does not appear to have developed critical thinking skills of students, this is because learning does not provide opportunities for students to identify problems and conclude new ideas or a observational act. The process of learning biology in schools does not encourage students to think critically. The research objective was to analyze the improvement of critical thinking skills by using the discovery learning model combined with constructivism-based modulesin on the excretory system concept. The method used was a quasi-experimental, pretest posttest design non-equivalent control group design. The population in this study were 156 students of class 11th MIPA who came from two schools, while the sample was 104 taken by purposive sampling.The instrument used was a reasoned multiple choice question accompanied by a rubric. The data analysis used was n-gain and independent sample t-test. The results showed that the critical thinking skills obtained was 0.78, with an increase in class critical thinking skills including the high category. This shows that there are differences in the critical thinking skills of students between the experimental class and the control class on excretory system concept in class 11thSMAN 1 Kluet Utara and SMAN 1 Kluet Selatan. Thus, the implementation of discovery learning model combined with constructivism-based modulescan improve students' critical thinking skills on excretory system concept.